The Deep Mixing Method: Bearing Capacity Studies - A. Rashid, A. S. (Springer International Publishing, 2017)
Nowadays, several techniques are employed to improve the problem of carrying out construction in soft soils by increasing the strength of the soil foundation and reducing the settlement of the soil. Among these stabilizing techniques, the deep mixing method is regarded as the most popular. The deep mixing method is a soil modification method where the soil is mixed in situ with stabilizing agents, commonly soil–cement columns. It increases the strength of the soil, providing bearing resistance and improved settlement performance. Deep mixing is carried out in situ using a machine equipped with mixing blades mounted at the end of a tube that has a nozzle at the lower end. The stabilizer agent is injected into the soil via the nozzle using a pumping system so that it mixes with the soil as the blades are rotated. Throughout this paper, previous works by numerous researchers on deep mixing including laboratory work, full-scale field tests, analytical and numerical analyses related to bearing capacity are reviewed. The techniques and results used are discussed with the help of figures depicting charts, failure modes, and the model configuration setup. It was found that the deep mixing method is suitable for use with any type of soil and provides a better alternative to the existing method of improving soft clay ground, especially with regard to the soil bearing capacity. In addition, future research is needed to improve the use of the method for soil improvement in the construction industry.